Omicron variant infection in inflammatory rheumatological conditions – outcomes from a COVID-19 naive population in Aotearoa New ZealandResearch in context - Jonathon Brooks; Anna Montgomery; Nicola Dalbeth; Mark Sapsford; Rachel Ngan Kee; Amy Cooper; Vicki Quincey; Suleman Bhana; Monique Gore-Massy; Jonathan Hausmann; Jean Liew; Pedro M. Machado; et al. (The Lancet Regional Health. Western Pacific, 2023)
Summary: Background: Due to geographic isolation and border controls Aotearoa New Zealand (AoNZ) attained high levels of population coronavirus disease-19 (COVID-19) vaccination before widespread transmission of COVID-19. We describe outcomes of SARS-CoV-2 infection (Omicron variant) in people with inflammatory rheumatic diseases in this unique setting. Methods: This observational study included people with inflammatory rheumatic disease and SARS-CoV-2 infection in AoNZ between 1 February and 30 April 2022. Data were collected via the Global Rheumatology Alliance Registry including demographic and rheumatic disease characteristics, and COVID-19 vaccination status and outcomes. Multivariable logistic regression was used to explore associations of demographic and clinical factors with COVID-19 hospitalisation and death. Findings: Of the 1599 cases included, 96% were from three hospitals that systematically identified people with inflammatory rheumatic disease and COVID-19. At time of COVID-19, 1513 cases (94.6%) had received at least two COVID-19 vaccinations. Hospitalisation occurred for 104 (6.5%) cases and 10 (0.6%) patients died. Lower frequency of hospitalisation was seen in cases who had received at least two vaccinations (5.9%), compared to the unvaccinated (20.6%) or those with a single vaccine dose (10.7%). In multivariable adjusted models, people with gout or connective tissue diseases (CTD) had increased risk of the combined outcome of hospitalisation/death, compared to people with inflammatory arthritis. Glucocorticoid and rituximab use were associated with increased rates of hospitalisation/death. All patients who died had three or more co-morbidities or were over 60 years old. Interpretation: In this cohort with inflammatory rheumatic diseases and high vaccination rates, severe outcomes from SARS-CoV-2 Omicron variant were relatively infrequent. The outcome of Omicron variant infection among vaccinated but SARS-CoV-2 infection-naive people with inflammatory rheumatic disease without other known risk factors were favourable. Funding: Financial support from the American College of Rheumatology (ACR) and European Alliance of Associations for Rheumatology (EULAR) included management of COVID-19 Global Rheumatology Alliance funds.